Topography of terror : Gestapo, SS and Reich Security Main Office on Wilhelm-and Prinz-Albrecht-Strasse : a documentation / published by Topography of Terror Foundation (Stiftung Topographie des Terrors)
Bibliografía: p. 267. Índices